Strategi Pemberdayaan UKM Tenun Tradisional di Sukarara Lombok Tengah Melalui Pelatihan Digital Marketing dan Branding Produk Lokal - Jauhari, Lalu Ahmad; Febri, Sintia (Lembaga Publikasi Ilmiah Nusantara, 2025)
Sukarara, Central Lombok, is renowned as a hub for traditional woven fabrics rich in cultural and economic value. However, SMEs (Small and Medium Enterprises) in this sector often face challenges in marketing their products, especially in the digital marketplace. This study aims to formulate an empowerment strategy for traditional weaving SMEs through digital marketing training and local product branding. The research employed a participatory approach with SME actors, including needs identification, intensive training, and mentoring in the implementation of digital marketing strategies. The results showed that the training enhanced SME actors' skills in utilizing social media, creating creative content, and leveraging local cultural values as market appeals. This strategy effectively expanded market reach, increased income, and strengthened the positioning of local products in the global market. This research is expected to serve as a model for culturally-based SME empowerment programs in other regions.